Quota Formula Review : Initial Considerations. (Policy Papers; Policy Paper ;, 2012)
The Board of Governors has asked the Executive Board to complete a comprehensive review of the quota formula by January 2013. This review is an mportant part of the 2010 quota and governance reforms. At the Seoul Summit, G-20 Leaders welcomed the reforms, which they noted include 'Continuing the dynamic process aimed at enhancing the voice and representation of emerging market and developing countries, including the poorest, through a comprehensive review of the quota formula by January 2013 to better reflect the economic weights; and through completion of the next general review of quotas by January 2014.' At its most recent meeting in September 2011, the IMFC stressed that governance reform is crucial to the legitimacy and effectiveness of the IMF. The IMFC committed to intensify its efforts to meet the 2012 Annual Meetings target for effectiveness of the 2010 reform, and called for a report on progress in the quota formula review by the time of its next meeting.